Digital infrastructure policies, local fiscal and financing constraints of Non-SOEs: Evidence from China - Yuwei Liu; Sheng Ma; Mei Sun (PLoS ONE, 2025)
Digital infrastructure serves as a cornerstone of urban digital transformation and smart city development, yet its implications for local fiscal systems and micro-level enterprises remain underexplored. This study empirically investigates the impact of digital infrastructure policies on the financing constraints of Non-SOEs in China. The contributions of this paper are as follows: (1) Theoretical innovation: It develops a comprehensive theoretical framework connecting macro-level digital policies, regional fiscal dynamics, and micro-enterprise financing constraints, offering a novel perspective on how macro policies influence micro-enterprises. (2) Systemic analysis: It enhances understanding of the systemic effects of digital infrastructure policies by demonstrating their ability to alleviate financing constraints through mitigating fiscal burdens, improving budgetary revenue quality, and strengthening regional financial development. Analysis of heterogeneity reveals that digital infrastructure policies implemented by Chinese provincial governments are particularly effective. (3) Practical insights: It offers practical guidance for policymakers to design targeted strategies that reduce financing constraints and support private sector growth in the digital economy. Non-SOEs in the growth and decline periods benefit more from digital infrastructure due to higher financing demands. Non-SOEs independent of SOEs in the supply chain are more responsive to digital infrastructure, effectively alleviating financing constraints. Moreover, the construction of digital infrastructure is highly conducive to the attraction of Non-SOEs and does not result in the vertical imbalances in local fiscals that are associated with traditional infrastructure construction. This evidence offers valuable guidance for local governments to optimize digital transformation policies and foster private economy growth.